KARAKTERISTIK FISIKOKIMIA DAN SENSORI SELAI BENGKUANG DENGAN PENAMBAHAN KULIT BUAH NAGA MERAH SEBAGA PEWARNA ALAMI - Nadya Mara Adelina; Wasiatul Maghfiroh; Bidadari Kiara Ramadhani Lubis; Nabila Kilka Ramadhan (Faculty of Agriculture Science & Technology, 2022)
Jicama (Pachyrhizus erosus) has a huge potential to be developed as an ingredient of processed food. The high content of nutrition compounds possessed by jicama could be utilized to produce health products, such as jam. However, the product developed using jicama has a less attractive sensory characteristic, especially for their color. On the other hand, dragon fruit peel is a waste product containing high fiber, vitamin C, and anthocyanin, which is the natural red pigment that can be used as natural colorant. The utilization of dragon fruit peel as a natural colorant for jicama jam aimed to improve the sensory properties and nutritional compounds of product. This research used four formulas of jicama jam with various ratios of additional dragon fruit peel. These results showed that the increasing ratio of dragon fruit peel to jam could significantly decrease the water content and acidity value (pH). However, total dissolved solids, vitamin C content, anthocyanin content, and antioxidant activity increased significantly as the increasing of dragon fruit peel ratio. Results for the sensory analyses concluded that the formula of jam with 40% of jicama and 60% of dragon fruit peel has the highest scores for all parameters evaluated among the others (color, taste, texture, aroma, overall). This formula has the characteristic of red-purple in color, water content 21.67%, acidity 3.27, total dissolved solids 65.14%, anthocyanin content 2.70 mg/100 g, vitamin C content 42.77 mg/100g, and IC50 for DPPH radical scavenging 44.52 mg/mL. This research was expected to boost the utilization of jicama and to improve the additional value of waste dragon fruit peel.